Nonlinear Dynamic Response of Nano-composite Sandwich Annular Spherical Shells - Nguyen, Dinh Duc (H. : ĐHQGHN, 2019)
In this research, the nonlinear dynamic response of functionally graded carbon nanotube reinforced composite (FG-CNTRC) sandwich annular spherical shells supported by Pasternak’ foundation is considered by using the analytical approach. Unlike existing works, the structure has three layers: FG-CNTRC layer – homogeneous core – FG-CNTRC layer. Several examples are considered to analyse the behaviour of this sandwich-structured composite. The classical shell theory (CST) is used to derive theoretical formulation delineating nonlinear dynamic response of FG-CNTRC sandwich annular spherical shells. The numerical results explain the effect of material, geometrical parameters, and elastic foundations on the nonlinear dynamic response of the annular spherical shell.